Rhetorical moves with tense and voice analysis of the results and discussion chapter in master theses across sciences - Dastjerdi, Zahra Shirian (2017)
There are well-established conventions within each academic discourse community that determine the structural organization of any related genre of that particular discourse community. As a specific genre in academic writing, writing a thesis is the most challenging task for postgraduate students especially the Integrated Results and Discussion chapter. In order to gain insight into Results and Discussion as integrated chapters of master’s theses, the present study investigated the rhetorical units of Integrated Results and Discussion chapters of master students in the hard and soft sciences as an undiscovered genre. Besides, the study also compared and contrasted the rhetorical units as well as the use of tense and voice of the investigated texts. To achieve the objectives of the study, a total of 40 master’s theses from a local public university in Malaysia were selected as the samples of the study. Of the 40 master’s theses, 20 theses were from the hard sciences (10 theses from Chemistry and 10 theses from Physics) and another 20 from the soft sciences (10 theses from English Language and 10 theses from Economics). Other criteria for selection were that all the theses had an Integrated Results and Discussion chapter and they were written within a period of 10 years from 2002 to 2012. To conduct the study, a mixedmethod approach was adopted. The quantitative analysis was conducted to locate the rhetorical movements of the corpus. As such, Kanoksilapatham’s (2005) analytical model was adapted to identify and highlight the employed rhetorical moves and steps of the study. The different rhetorical movements used in the hard sciences and soft sciences were compared based on the frequency of occurrence. Additionally, the study also examined the use of tense and voice in the rhetorical moves and steps of the corpora because according to Larsen-Freeman, Kuehn, and Haccius (1999), the choice of English tenses and voices is one of the most difficult grammatical areas for ESL students. To enhance the robustness of the methodology, the shift in the use of tense and voice in the rhetorical steps were investigated qualitatively. The findings of the study indicated that the Integrated Results and Discussion chapters focused predominantly on presenting the results of the study (Stating Results) followed by commenting on the gained results, which constituted Move 5 or Stating Comments on Result. These two moves together with their sub-units or steps constituted the most frequently used rhetorical units of the investigated texts. On the other hand, Stating Limitations and Suggesting Further Research were the least frequently used rhetorical units. A possible reason could be that the ESL student writers would prefer to communicate these two rhetorical units in the last chapter (Conclusion) of the theses. Disciplinary variation was also observed between the rhetorical movements used in the hard sciences and soft sciences. For instance, in the hard sciences, M3S2 (Referring to Previous Research) and M7S5 (Making Overt Claims or Generalizations) were obligatory. But they were found to be optional and in the soft sciences. On the other hand, in the soft sciences, M4S3 (Invalidating Results) was obligatory, but in the hard sciences, it was optional. In consequence, these results showed that the hard sciences had more tendencies towards providing subjective presentation than the soft sciences, and the soft sciences had more tendencies towards objective presentation than the hard sciences. Moreover, the analysis of tenses indicated that in both hard and soft sciences, the simple present tense was the preferred tense followed by the simple past tense. However, disciplinary variations were observed in the tense usage in the different rhetorical units. The most observable variations were found in Describing Aims and Purposes (with dominant use of the simple past tense in the hard sciences and the simple present tense in the soft sciences), Listing Procedures or Methodological Techniques (with dominant use of the simple past tense in the hard sciences and the simple present tense in the soft sciences), Invalidating Results (with dominant use of the simple past tense in the hard sciences and the simple present tense in the soft sciences), and Presenting Generalizations, Claims, Deductions, or Research Gaps (with dominant use of the simple future tense in the hard sciences and the simple present tense in the soft sciences). The contextual analysis revealed that the contributing factors in the choice of tense were temporal aspects, rhetorical unit function, type of science, and the structure of the report. Additionally, it was found that the frequency of use of the active voice outnumbered the passive voice in the overall use of the voice aspect in the corpus. The voice disciplinary variations were observed mostly in Structure of the Section (dominantly presented in the passive voice in the hard sciences and the active voice in the soft sciences), Describing Aims and Purposes (dominantly presented in the passive voice in the hard sciences and the active voice in the soft sciences), Listing Procedures or Methodological Techniques (dominantly presented in the passive voice in the hard sciences and the active voice in the soft sciences) and Referring to Previous Research (dominantly presented in the passive voice in the hard sciences and the active voice in the soft sciences). The influencing factors which governed the choice of voice in the corpus were the function of the step, the associated verb and tense, and the writers’ stance in the text. To conclude, it is hoped that the results of this study explain how Integrated Results and Discussion chapters in different sciences are organized rhetorically, which in turn, may be useful for the successful writing of the Integrated Results and Discussion chapters in master’s theses. Also, a thorough understanding of the full range of possible meanings and uses of the tenses and voices and how they can be applied to rhetorical uses in academic writing will allow the writer the greatest flexibility in the use of tense and voice to express nuances in meanings (Taylor, 2001).